Strategi Empat Konsensus Kebangsaan Bagi Pembangunan Generasi Muda Dalam Menyongsong Bonus Demografi Dan Implikasinya Terhadap Ketahanan Sosial Masyarakat Kepulauan Riau - Soesatyo, Bambang (Jurnal Ketahanan Nasional, 2024)
ABSTRACT The Demographic Bonus is a golden opportunity for the Indonesian nation. However, the existing social problems due to limited workforce pose a threat to this opportunity. Through the reconstruction of the Four Pillars of the Nation: (Pancasila, UUD 1945, Negara Kesatuan Republik Indonesia and Bhinneka Tunggal Ika) strengthening of the younger generation is implemented as a preventive measure and societal understanding. The research aims to determine how the Four Pillars of the Nation strategy is implemented for the development of the younger generation in facing the Demographic Bonus and its implications for the social resilience of the Riau Islands. Using a descriptive qualitative approach, the research informants involve academics, community leaders, youth figures, government, and private employees, as well as students. The results show that the Riau Islands Government strives through the Demographic Bonus and the strengthening of national values, but the threat of national disintegration arises. The socialization of the Four Pillars of the Nation needs improvement, especially among teachers and community leaders. Protection for communities vulnerable to human trafficking is carried out through the Trauma Center Protection House (RPTC) with the formation of a social network involving the TPPO Task Force and the Provincial Task Force. Challenges related to financial motivation and economic inequality still exist. The Four Pillars of the Nation are implemented as education on national values, and conflict resolution involves communication and sometimes legal approaches. Collaboration between the TPPO Task Force, the community, and community leaders is expected to reduce the risk of human trafficking in this province.